Arrangement Urgency of Medical Tourism Implementation at Bali Mandara Hospital - Bagiastra, I Nyoman (International Journal of Social Sciences and Management, 2017)
Policy arrangement and a good regulation related to medical tourism at Bali Mandara Hospital that was planned to operate in 2017 are extremely significant to do in order to minimize legal issues after being applied. Bali Mandara Hospital is an international-based health service facility managed by Bali Provincial Government. This international-based hospital’s superiority is medical tourism application. It is known that Bali has a huge comparative aspects to make as tourism destination either in national scale or international scale. Bali has the most-known geographical area by tourists because it has special cultural characteristics. Thus, understanding about Tourism Law philosophically, epistemologically, and axiologically is the main factor, especially for policy maker in determining the success of sustainable tourism development. Collaboration between tourism sector and health sector are the most possible thing to do, but in implementation process, clear regulation is really needed. Therefore, Bali is better to make a local regulation especially for the collaboration. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 115-119